Adaptive response and tolerance to weak acids in Saccharomyces cerevisiae boulardii: a metabolomics approach. (22nd February 2022) - Fu, Junjie; Liu, Chaolan; Li, Li; Liu, Jun; Tie, Yu; Wen, Xueping; Zhao, Qikai; Qiao, Zongwei; An, Zheming; Zheng, Jia
Summary: Weak acids inhibit the growth of probiotics, such as Saccharomyces boulardii . We explored the tolerance of S. boulardii to different weak acids. S. boulardii had better fermentation ability under lactic acid conditions compared with acetic and butyric acid conditions; however, the budding of S. boulardii was significantly stronger than that of Saccharomyces cerevisiae under acetic acid conditions. Although the surface structure of S. boulardii was destroyed, it produced more daughter cells. S. boulardii metabolites were also significantly different from S. cerevisiae under acidic stress. The growth of S. boulardii under weak acid conditions differed significantly from that of S. cerevisiae . S. boulardii ‐mediated fingerprints under weak acid conditions were identified as latent biomarkers, related to fructose and mannose metabolism, tricarboxylic acid cycle, and the glycolysis pathway. Identified biomarkers will aid in the genetic engineering of S. boulardii and other Saccharomyces strains for improved acid resistance and biomass yield. Abstract : Influence of weak acid on growth and metabolites of Saccharomyces boulardii .